Discrete Symmetries Analysis and Exact Solutions of the Inviscid Burgers Equation - Hongwei Yang; Yunlong Shi; Baoshu Yin; Huanhe Dong (Discrete Dynamics in Nature and Society)
We discuss the Lie point symmetries and discrete symmetries of the inviscid Burgers equation. By employing the Lie group method of infinitesimal transformations, symmetry reductions and similarity solutions of the governing equation are given. Based on discrete symmetries analysis, two groups of discrete symmetries are obtained, which lead to new exact solutions of the inviscid Burgers equation.